Bilateral chylothorax following reoperative central neck dissection for metastatic papillary thyroid cancer. (17th April 2018) - Sharma, Ashwyn K; Sahli, Zeyad T; Mathur, Aarti
Abstract : Locoregional recurrence of papillary thyroid cancer (PTC) can occur in up to 30% of patients within 10 years after initial treatment. Reoperative surgery can be challenging due to scarring, fibrosis and distorted anatomy and may be associated with increased complications compared with initial operations. Chylothorax is an extremely rare and potentially life-threatening complication that can be associated with neck dissections and thyroid surgery. In this report, we describe an unusual case of bilateral chylothorax following a left central neck dissection for recurrent PTC.